Digital leadership, Twitter and Pope Francis. Issue 1 (1st January 2016) - Narbona, Juan
ABSTRACT: The Internet reproduces and strengthens our model of social dialog. Just as in the physical world, the online public conversation and, above all, the ideological debate, requires leaders who can be a point of reference to either foster values or contradict them. The concept of leadership has drawn the attention of several studies concerning communication management. Leaders are neither all equal nor do they exercise leadership by means of the same tools. This article studies both the concept of digital leadership as a guide for online conversation and the use that microblogs, such as Twitter, can provide for this purpose. Among several public figures using Twitter, we have focused our study on the @Pontifex account to have an insight into the type of leadership exercised by the Holy Father and the impact of his teaching. The analysis shows that the Pope uses Twitter for catechetical purposes and that he is aware that his message can reach a large audience. Moreover, although interaction between the Pope and his followers on this platform is a fact already known, we have further found that some messages arouse followers' interest more than others do.